PENGARUH MOTIVASI DAN KOMUNIKASI TERHADAP SEMANGAT KERJA KARYAWAN PADA HOTEL IBIS STYLES BALI PETITENGET - I Putu Juliarta Ananjaya; I Putu Bagus Suthanaya (Universitas Triatma Mulya, 2020)
Every company definitely wants the employee morale to continue to increase, which of course will have an impact on the company's profits. The problem raised in this study is whether motivation influences employee morale at Ibis Styles Bali Petitenget Hotel, does communication influence employee morale at Ibis Styles Bali Petitenget Hotel and what is the influence of motivation and communication on employee morale at Ibis Styles Bali Hotels Petitenget. This study uses the entire population as a sample or as many as 60 people. The data analysis technique used is descriptive analysis, test the quality of data that is validity and reliability test, classic assumption test, multiple linear regression analysis, t-test test and analysis of determination. The results of this study indicate that Motivation and Communication have a positive and significant effect on Employee Morale at Ibis Styles Bali Petitenget Hotels.